Metal ion doping method for enhancing electrochromic cycling stability of titanium dioxide and product thereof
Through the metal ion doping method, the use of secondary hydrothermal technology to combine cobalt or copper elements with titanium dioxide, solving the problem of insufficient cyclic stability performance of titanium dioxide electrochromic materials, and achieving efficient electrochromic and structural stability of the material.
Patent Information
- Application Number
- CN202411524463.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
Titanium dioxide electrochromic materials have defects in their cyclic stability properties, resulting in limited applications in the field of electrochromic.
The metal ion doping method is adopted to combine the transition group metal salt of cobalt or copper elements with titanium dioxide in an alkaline environment through secondary hydrothermal technology to form a stable metal ion doped titanium dioxide film.
It significantly improves the cyclic stability of titanium dioxide electrochromic materials, enhances ion transport performance, and maintains structural stability, making it suitable for large-scale commercial manufacturing.
Smart Images

Figure CN119430676A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochromic composite materials, and in particular to a metal ion doping method for enhancing the electrochromic cycle stability performance of titanium dioxide and a product thereof. Background Art
[0002] Titanium dioxide (TiO2) is a common transition metal oxide that appears light blue in the colored state and colorless in the bleached state. It has the advantages of excellent chemical stability, low price and environmental friendliness, so it has broad application prospects in the field of electrochromism. However, TiO2 itself also has inherent defects such as poor cycle stability, long coloring / bleaching response time, and small light modulation amplitude, which to some extent limit its large-scale practical application in the field of electrochromism.
[0003] In recent years, researchers have prepared titanium dioxide nanomaterials with various structures, such as nanorods, nanotubes, and nanostrip fibers, by optimizing and improving synthesis conditions. This type of one-dimensional structure has a large aspect ratio and specific surface area, and has significant advantages in promoting the diffusion and transmission of ions and electrons in the electrochromic process. It has also improved the inherent defects of titanium dioxide materials such as small light modulation amplitude and long response time to a certain extent. However, the problem of poor cyclic stability of single titanium dioxide electrochromic materials has not been effectively solved.
[0004] There are more and more studies on further improving the electrochromic performance of titanium dioxide by element doping or material composite. For example, the Chinese invention patent with publication number CN109704592A discloses a fluorine-doped titanium dioxide nanoarray electrochromic film and its preparation method. The preparation method of the film is specifically as follows: step 1, preparing a composite sol C containing Ti-F elements; step 2, pulling to prepare a gel film; step 3, placing a photosensitive gel film substrate with fluorine-doped titanium dioxide in a four-beam laser interference system for exposure; step 4, placing the exposed fluorine-doped titanium dioxide photosensitive gel film substrate in a solvent for washing, washing and removing the unexposed part, and obtaining a fluorine-doped titanium dioxide nanoarray gel film substrate; step 5, placing the fluorine-doped titanium dioxide nanoarray gel film substrate in a muffle furnace and vacuum annealing at 450 ° C for 60 min to obtain a fluorine-doped titanium dioxide nanoarray electrochromic film. This scheme uses soda-lime glass as the substrate, and covers the substrate with a fluorine-doped titanium dioxide nanoarray electrochromic film. The fluorine element is doped into the titanium dioxide array film through a complex sol-gel method, laser interference method and subsequent heat treatment, which improves the electrochromic performance of titanium dioxide to a certain extent, but still fails to solve the defect of poor cyclic stability performance.
[0005] The Chinese invention patent with publication number CN113736445A provides a porous crystalline / amorphous titanium dioxide electrochromic material and its preparation method and application. A porous crystalline / amorphous titanium dioxide electrochromic material is prepared by preparing a titanium source precursor solution and using a solvothermal method to form a porous mixed crystal structure of crystalline titanium dioxide and amorphous titanium dioxide and depositing it on a FTO conductive glass substrate. The amorphous titanium oxide and crystalline titanium oxide tissues form a mixed crystal structure through interface contact, which improves the electrochromic performance and can achieve rapid reversible transformation from transparent to dark green at low voltage. In addition, the Chinese invention patent with publication number CN113800781A discloses a tungsten trioxide-titanium dioxide electrochromic film and its preparation method. Using conductive glass as a substrate, a layer of TiO2 array film is prepared by a hydrothermal method; a secondary hydrothermal reaction is performed to grow WO3 on the TiO2 array to prepare the WO3-TiO2 electrochromic film. It uses the gaps and surfaces of the TiO2 array covered with WO3 nanorods and nanocrystals to increase the specific surface area of the film and shorten the diffusion path of ions; in addition, WO3 is mainly a monoclinic intercalated water structure, which can also be used to reduce the energy barrier for ion diffusion and increase ion flux. However, the above two technical solutions using composite structures also have the common problem of poor cycle stability. The reason. Whether it is a crystalline or amorphous composite, or a composite of tungsten trioxide and titanium dioxide, it is a direct and simple composite of substances and substances. This composite is loose and unstable in structure. Although the composite structure heterojunction and the larger surface area will improve the electrochromic performance in some aspects, this loose composite structure between substances is very easy to form structural collapse after multiple electrochemical cycles, resulting in the inability to obtain good cycle performance.
[0006] In summary, on the basis of meeting the electrochromic performance, seeking a method to improve the cyclic stability of titanium dioxide electrochromic film to make it more suitable for large-scale commercial manufacturing of titanium dioxide electrochromic glass is of great significance for expanding its application in the field of electrochromic composite materials. Summary of the invention
[0007] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide with convenient process and significant effect is provided, comprising the following steps: (1) titanium dioxide is subjected to a hydrothermal reaction in an alkaline solution environment. After the reaction is completed, the obtained crude product is purified to obtain a first hydrothermal product; (2) the first hydrothermal product undergoes a hydrothermal reaction with a transition metal salt containing cobalt or copper in an alkaline solution environment. After the reaction is completed, the product is kept at 130-160° C., and the obtained crude product is purified to obtain a second hydrothermal product. (3) treating the second hydrothermal product with an acid solution to complete ion replacement, and purifying the crude product after the treatment to obtain an ion replacement product; (4) dispersing the ion replacement product in a solution environment to form a product dispersion, coating the product dispersion on the surface of a substrate, and obtaining a metal ion-doped titanium dioxide film after drying and calcining.
[0008] In the field of electrochromism, titanium dioxide is usually used as a powdered raw material. Those skilled in the art can select a suitable type of titanium dioxide according to actual conditions, including commercial P25, high-purity electronic grade titanium dioxide, etc.
[0009] Preferably, in step (1), the amount of titanium dioxide used is 6-10 g; and the alkali concentration of the alkaline solution environment is 6-15 mol / L.
[0010] Furthermore, the alkaline solution environment is created by an aqueous solution of sodium hydroxide or potassium hydroxide.
[0011] Preferably, in step (1), the temperature of the hydrothermal reaction is 120-150° C., and the reaction time is 24-48 h.
[0012] The electrochromic process is similar to the working principle of lithium-ion batteries. Both use the embedding and extraction of ions to achieve coloring and bleaching changes under redox reactions. Therefore, from a mechanistic point of view, it is ideal to obtain samples with better cycle performance, improve the ion transmission performance of the samples, and create a structure that is conducive to ion embedding and extraction. If the element content of metal ions in TiO2 film is too small, it is not enough to show the effect, and if it is too much, it will block the ion transmission channel and cause performance degradation. Therefore, the appropriate doping amount is particularly important. Under the appropriate cobalt or copper doping amount, the ion transmission performance of TiO2 is improved, and the morphological structure does not change significantly, ensuring the structural stability during multiple electrochemical cycles. In addition, compared with non-metallic element doping, metal ions embedded in the lattice are not easy to separate from the body and have better stability.
[0013] Preferably, in step (2), the alkali concentration of the alkaline solution environment is 10-15 mol / L; and the molar mass ratio of the transition metal salt containing cobalt or copper element to titanium dioxide is 0.1%-5.0%.
[0014] Further preferably, the alkaline solution environment is created by an aqueous solution of potassium hydroxide or sodium hydroxide.
[0015] Further preferably, the transition metal salt containing cobalt or copper element includes at least one of cobalt acetate, cobalt chloride, copper acetate and copper chloride.
[0016] Preferably, in step (2), the temperature of the hydrothermal reaction is 180-220°C, and the reaction time is 6-24 h; after the reaction is completed, the temperature is lowered to the insulation treatment temperature at a rate of 1-3°C / min.
[0017] Preferably, in step (2), the heat preservation treatment time is 10-20 h.
[0018] Preferably, in step (3), the concentration of the acid solution is 0.1-0.5 mol / L.
[0019] Further preferably, the acid solution includes hydrochloric acid or sulfuric acid.
[0020] Preferably, in step (3), the ion replacement is carried out under stirring conditions, and the treatment time is 3-9 h.
[0021] The use of a polyethylene glycol / isopropanol mixed solution can better achieve the dissolution and dispersion of titanium dioxide and its doped composites, so that the product dispersion has the advantages of high transparency, firm adhesion, and not easy to fall off under visible light after being scraped.
[0022] Preferably, in step (4), the ion exchange product is dispersed in water, and then a polyethylene glycol / isopropanol mixed solution is added to prepare a product dispersion.
[0023] Further preferably, in the polyethylene glycol / isopropanol mixed solution, the volume ratio of polyethylene glycol to isopropanol is 0.5-2.0:1.
[0024] Preferably, in step (4), the concentration of the ion exchange product in the product dispersion is 0.005-0.01 g / mL.
[0025] Preferably, in step (4), the calcination temperature is 350-500°C and the calcination time is 2-4 h.
[0026] In the above operation, those skilled in the art can select suitable raw material mixing, product recovery or purification and other treatment methods according to the actual production scale or conditions, or determine the amount of processing additives. For example, the reaction product is washed to neutral and then dried, and grinding is performed when necessary to make the obtained product meet the use requirements. The process of coating the product dispersion on the surface of the substrate is diverse, and its selection varies based on the conditions and scale of preparation, and suitable methods such as scraping and spin coating can be used. As presented in one or more embodiments of the present invention, under laboratory preparation conditions, scraping becomes a particularly suitable processing method because of its convenient and fast characteristics. For commercially available common substrate specifications, such as FTO conductive glass, 60-150 μL of product dispersion can be used, and those skilled in the art can also select a suitable coating amount according to demand and production scale. Similar to the immersion treatment, when a hydrothermal reaction is carried out in an alkaline solution environment, treated with an acid solution, and dispersed in a solution environment to form a product dispersion, based on the general understanding principle of the above-mentioned treatment in the art, the amount of liquid is excessive relative to the added raw materials.
[0027] In the second aspect of the present invention, a metal ion-doped titanium dioxide film with good electrochromic performance and excellent cycle stability is provided, which is made by the metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to the first aspect of the present invention.
[0028] As described in the prior art, metal ions play an important role in reducing the band gap of materials and promoting the separation of photogenerated charges. The combination of metal ions and TiO2 is not difficult to achieve in experiments, but how to combine cobalt and copper metal ions with the one-dimensional structure of TiO2 with electrochromic properties to enhance its cycle performance is a technical obstacle that the present invention needs to overcome.
[0029] Based on the above technical scheme, the design concept and principle of the present invention is that the process method adopts secondary hydrothermal technology. In the primary hydrothermal stage, the alkaline conditions used are relatively mild, the concentration is low, and the reaction temperature is low, thereby forming a primary one-dimensional structure with imperfect structure and crystal form, which helps to effectively allow the added metal salt to enter the titanium oxide lattice under the conditions of high heat and high alkali concentration in the secondary hydrothermal process. After the hydrothermal reaction, keeping the temperature at a relatively low temperature for a period of time helps to form a one-dimensional structure with a longer aspect ratio, so that the crystal form and structure of the one-dimensional structure finally formed are stable.
[0030] The stability of the morphology plays a vital role in the cycle performance. Different from direct and simple compounding, the present invention adopts ion doping to allow a small amount of ions to directly enter the TiO2 lattice to form a stable crystal structure. The doped metal ions partially enter the TiO2 lattice, which does not have a great impact on the morphology of TiO2 itself, but effectively improves the ion diffusion rate (the ion diffusion coefficient of TiO2 film is 3.98×10-10 cm 2 / s, while the samples doped with 1% cobalt and copper ions reached 8.6×10 -10 cm 2 / s and 9.1×10 -10 cm 2 / s), which significantly enhances the electrochemical activity of the composite film and maintains structural stability. This not only improves the ion transport performance, but also does not easily destroy the morphology structure, thereby enhancing the cycle stability of the TiO2 electrochromic material.
[0031] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide, which has a convenient process and significant effect and is suitable for large-scale commercial production.
[0032] The present invention provides a metal ion-doped titanium dioxide film, which has high transparency, firm adhesion and is not easy to fall off; the film has a one-dimensional structure, which is conducive to the rapid transmission of electrons and ions. After being doped with metal ions, the cycle performance is significantly enhanced, and it has the characteristics of good electrochromic performance and excellent cycle stability performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 The scanning electron microscope (SEM) image of the metal ion-doped titanium dioxide film prepared in Example 1; wherein (a) is a front view and (b) is a side cross-sectional view; Figure 2 The light modulation amplitude diagram of the coloring / bleaching state of the metal ion-doped titanium dioxide film prepared in Example 1 under -1.6 V and 1.0 V bias; Figure 3 This is an in-situ variation diagram of the light transmittance of the metal ion-doped titanium dioxide film prepared in Example 1 measured at 633 nm under bias voltages of -1.6 V and 1.0 V; Figure 4 200 cycles comparison diagram of the undoped pure phase titanium dioxide film and the metal ion doped titanium dioxide film prepared in Example 1; wherein (a) is the undoped pure phase titanium dioxide film, and (b) is the metal ion doped titanium dioxide film; Figure 5 200 cycle comparison diagram of the undoped pure phase titanium dioxide film and the metal ion doped titanium dioxide film prepared in Example 2; wherein (a) is the undoped pure phase titanium dioxide film, and (b) is the metal ion doped titanium dioxide film. DETAILED DESCRIPTION
[0034] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0035] Example 1 A metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide, comprising the following steps: (1) 8 g of commercial P25 titanium dioxide powder was added to a 10 mol / L NaOH solution, stirred and dispersed, and then subjected to a hydrothermal reaction at 130 °C for 36 h. The crude product after the reaction was washed to neutrality, dried and collected to obtain a first hydrothermal product; (2) The first hydrothermal product was added to a 15 mol / L KOH solution, stirred and dispersed, and then cobalt acetate with a molar mass ratio of 0.5% (relative to titanium dioxide) was added to carry out a hydrothermal reaction at 200 °C for 24 h, then cooled to 150 °C at a rate of 1 °C / min and kept for 12 h, quenched and cooled to room temperature, and the product was washed to neutrality, dried and collected to obtain a second hydrothermal product; (3) adding the second hydrothermal product to 0.1 mol / L hydrochloric acid and stirring for 6 h to complete the ion replacement, then washing the crude product to neutrality, grinding it, and drying and collecting it to obtain an ion replacement product; (4) The ion exchange product was ultrasonically dispersed in deionized water, and then a polyethylene glycol / isopropanol mixed solution (1:2, v / v) was added to prepare a product dispersion. 100 μL of the product dispersion with a concentration of 0.006 g / mL was scraped on an FTO conductive glass substrate. After drying and dehydration, the resulting film was calcined at 400 °C for 2 h to obtain a titanium dioxide film doped with 0.5% cobalt metal ions, i.e., a metal ion-doped titanium dioxide film.
[0036] Example 2 A metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide, comprising the following steps: (1) 8 g of commercial P25 titanium dioxide powder was added to a 10 mol / L NaOH solution, stirred and dispersed, and then subjected to a hydrothermal reaction at 130 °C for 36 h. The crude product after the reaction was washed to neutrality, dried and collected to obtain a first hydrothermal product; (2) The first hydrothermal product was added to a 15 mol / L KOH solution, stirred and dispersed, and then copper acetate with a molar mass ratio of 1.0% (relative to titanium dioxide) was added to carry out a hydrothermal reaction at 200 °C for 24 h, then cooled to 150 °C at a cooling rate of 1 °C / min for 12 h, quenched and cooled to room temperature, and the product was washed to neutrality, dried and collected to obtain a second hydrothermal product; (3) adding the second hydrothermal product to 0.1 mol / L hydrochloric acid and stirring for 6 h to complete the ion replacement, then washing the crude product to neutrality, grinding it, and drying and collecting it to obtain an ion replacement product; (4) The ion exchange product was ultrasonically dispersed in deionized water, and then a polyethylene glycol / isopropanol mixed solution (1:2, v / v) was added to prepare a product dispersion. 100 μL of the product dispersion with a concentration of 0.006 g / mL was scraped on an FTO conductive glass substrate. After drying and dehydration, the substrate was calcined at 400 °C for 2 h to obtain a titanium dioxide film doped with 1.0% copper metal ions, i.e., a metal ion-doped titanium dioxide film.
[0037] Example 3 A metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide, comprising the following steps: (1) 6 g of high-purity electronic grade titanium dioxide powder was added to a 6 mol / L KOH solution, stirred and dispersed, and then subjected to a hydrothermal reaction at 150 °C for 24 h. The crude product after the reaction was washed to neutrality, dried and collected to obtain a first hydrothermal product; (2) The first hydrothermal product was added to a 10 mol / L NaOH solution, stirred and dispersed, and then cobalt chloride with a molar mass ratio of 0.1% (relative to titanium dioxide) was added to carry out a hydrothermal reaction at 220 °C for 6 h, then cooled to 130 °C at a rate of 3 °C / min and kept for 20 h, quenched and cooled to room temperature, and the product was washed to neutrality, dried and collected to obtain a second hydrothermal product; (3) adding the second hydrothermal product to 0.1 mol / L sulfuric acid and stirring for 3 h to complete the ion replacement, then washing the crude product to neutrality, grinding it, and drying and collecting it to obtain an ion replacement product; (4) The ion exchange product was ultrasonically dispersed in deionized water, and then a polyethylene glycol / isopropanol mixed solution (2:1, v / v) was added to prepare a product dispersion. 60 μL of the product dispersion with a concentration of 0.001 g / mL was scraped and coated on the FTO conductive glass substrate. After drying and dehydration, the substrate was calcined at 350 °C for 4 h to obtain a metal ion-doped titanium dioxide film.
[0038] Example 4 A metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide, comprising the following steps: (1) 10 g of commercial P25 titanium dioxide powder was added to a 15 mol / L NaOH solution, stirred and dispersed, and then subjected to a hydrothermal reaction at 120 °C for 48 h. The crude product after the reaction was washed to neutrality, dried and collected to obtain the first hydrothermal product; (2) The first hydrothermal product was added to a 15 mol / L KOH solution, stirred and dispersed, and then copper chloride with a molar mass ratio of 5.0% (relative to titanium dioxide) was added to carry out a hydrothermal reaction at 180 °C for 24 h, then cooled to 160 °C at a rate of 1 °C / min and kept for 10 h, quenched and cooled to room temperature, and the product was washed to neutrality, dried and collected to obtain a second hydrothermal product; (3) adding the second hydrothermal product to 0.5 mol / L hydrochloric acid and stirring for 9 h to complete the ion replacement, then washing the crude product to neutrality, grinding it, drying it, and collecting it to obtain an ion replacement product; (4) The ion exchange product was ultrasonically dispersed in deionized water, and then a polyethylene glycol / isopropanol mixed solution (1:2, v / v) was added to prepare a product dispersion. 150 μL of the product dispersion with a concentration of 0.005 g / mL was scraped onto the FTO conductive glass substrate. After drying and dehydration, the film was calcined at 500 °C for 2 h to obtain a metal ion-doped titanium dioxide film.
[0039] Comparative Example 1 In this comparative example, a similar method was used to prepare an undoped pure phase titanium dioxide film for comparative study, and the steps were as follows: (1) 8 g of commercial P25 titanium dioxide powder was added to a 10 mol / L NaOH solution, stirred and dispersed, and then subjected to a hydrothermal reaction at 130 °C for 36 h. The crude product after the reaction was washed to neutrality, dried and collected to obtain a first hydrothermal product; (2) The first hydrothermal product was added to a 15 mol / L KOH solution, stirred and dispersed, and then subjected to a hydrothermal reaction at 200 °C for 24 h. The temperature was then reduced to 150 °C at a rate of 1 °C / min and kept at that temperature for 12 h. The product was quenched and cooled to room temperature. The product was washed to neutrality and dried to obtain a second hydrothermal product. (3) adding the second hydrothermal product to 0.1 mol / L hydrochloric acid and stirring for 6 h to complete the ion replacement, then washing the crude product to neutrality, grinding it, and drying and collecting it to obtain an ion replacement product; (4) The ion exchange product was ultrasonically dispersed in deionized water, and then a polyethylene glycol / isopropanol mixed solution (1:2, v / v) was added to prepare a product dispersion. 100 μL of the product dispersion with a concentration of 0.006 g / mL was scraped and coated on a FTO conductive glass substrate. After drying and dehydration, the film was calcined at 400 °C for 2 h to obtain an undoped pure phase titanium dioxide film.
[0040] The surface and cross-sectional morphologies of the metal ion-doped titanium dioxide film prepared in Example 1 were observed using a scanning electron microscope. The images are as follows: Figure 1 (a) and (b) are shown. The target one-dimensional nanostructured film is prepared by the method of the present invention. The light transmittance of the metal ion-doped titanium dioxide film in the colored state and the bleached state is tested at -1.6 V and 1.0 V bias voltages, respectively. The results are shown in FIG. Figure 2 shown. Figure 2 It shows that the light modulation amplitude of the titanium dioxide film doped with 0.5% cobalt metal ions reaches 35%. Then the in-situ change of its light transmittance at 633 nm under -1.6 V and 1.0 V bias was tested. The results are as follows Figure 3 shown. Figure 3 The fastest coloring time of the sample is 1.92 s. In order to study the cyclic stability of the film, the undoped pure phase titanium dioxide film was used as a control to carry out cyclic performance tests. The results are as follows Figure 4 As shown. Figure 4 It can be seen that the performance of the titanium dioxide film doped with 0.5% cobalt metal ions has not declined after 200 cycles, and the cycle stability performance is significantly improved compared with the undoped pure phase titanium dioxide film.
[0041] The same method was used to test the light transmittance of the metal ion-doped titanium dioxide film of Example 2 in the colored state and the bleached state at -1.6 V and 1.0 V bias voltages, respectively, and the light modulation amplitude reached 40%. The in-situ change of the light transmittance of the film at 633 nm under -1.6 V and 1.0 V bias voltages showed that its fastest coloring time was 1.95 s. Figure 5 As shown, further cycle performance tests indicate that the performance of the titanium dioxide film doped with 1% copper metal ions has not declined after 200 cycles, and the cycle stability performance is significantly improved compared with the undoped pure phase titanium dioxide film.
[0042] The secondary hydrothermal technology proposed in the present invention can transform common commercial P25 powder and high-purity electronic grade titanium dioxide powder into a one-dimensional nanostructure, so that it has good electrochromic performance. The preparation method using a polyethylene glycol / isopropyl alcohol mixed solution can better achieve the dissolution and dispersion of titanium dioxide and its doped composites. After being scraped, the dispersion has high transparency under visible light, strong adhesion, and is not easy to fall off.
[0043] The maximum light modulation amplitude of the cobalt metal ion doped titanium dioxide electrochromic film prepared by the present invention reaches 35%, the fastest coloring time is 1.92 s, and the light modulation amplitude does not decrease after 200 cycles of the optimal amount of doped film, and the cycle performance of the undoped film sample is significantly improved. Correspondingly, the maximum light modulation amplitude of the copper metal ion doped titanium dioxide electrochromic film reaches 40%, the fastest coloring time is 1.95 s, and the light modulation amplitude does not decrease after 200 cycles of the optimal amount of doped film, and the cycle performance of the undoped film sample is significantly improved.
[0044] In summary, the present invention adopts ion doping to allow a small amount of ions to directly enter the TiO2 lattice, forming a stable crystal structure. The doped metal ions partially enter the TiO2 lattice, which does not have a significant impact on the morphology of TiO2 itself, but effectively improves the ion diffusion rate, significantly enhances the electrochemical activity of the composite film, and maintains structural stability, which not only improves the ion transmission performance, but also does not destroy the morphology structure, thereby enhancing the cycle stability of the TiO2 electrochromic material.
[0045] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.
Claims
1. A metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide, characterized in that: The steps include: (1) titanium dioxide is subjected to a hydrothermal reaction in an alkaline solution environment. After the reaction is completed, the obtained crude product is purified to obtain a first hydrothermal product; (2) the first hydrothermal product undergoes a hydrothermal reaction with a transition metal salt containing cobalt or copper in an alkaline solution environment. After the reaction is completed, the product is kept at 130-160° C., and the obtained crude product is purified to obtain a second hydrothermal product. (3) treating the second hydrothermal product with an acid solution to complete ion replacement, and purifying the crude product after the treatment to obtain an ion replacement product; (4) dispersing the ion replacement product in a solution environment to form a product dispersion, coating the product dispersion on the surface of a substrate, and obtaining a metal ion-doped titanium dioxide film after drying and calcining.
2. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (1), the amount of titanium dioxide used is 6-10 g; the alkali concentration of the alkaline solution environment is 6-15 mol / L; and the alkaline solution environment is created by an aqueous solution of sodium hydroxide or potassium hydroxide.
3. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (1), the temperature of the hydrothermal reaction is 120-150°C and the reaction time is 24-48 hours.
4. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (2), the alkali concentration of the alkaline solution environment is 10-15 mol / L; the molar mass ratio of the transition metal salt containing cobalt or copper elements to titanium dioxide is 0.1%-5.0%; the alkaline solution environment is created by an aqueous solution of potassium hydroxide or sodium hydroxide; the transition metal salt containing cobalt or copper elements includes at least one of cobalt acetate, cobalt chloride, copper acetate, and copper chloride.
5. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (2), the temperature of the hydrothermal reaction is 180-220°C, and the reaction time is 6-24 h. After the reaction is completed, the temperature is lowered to the insulation treatment temperature at a rate of 1-3°C / min. The insulation treatment time is 10-20 h.
6. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (3), the concentration of the acid solution is 0.1-0.5 mol / L; the acid solution includes hydrochloric acid and sulfuric acid; the ion replacement is carried out under stirring conditions, and the treatment time is 3-9 hours.
7. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (4), the ion exchange product is dispersed in water, and then a polyethylene glycol / isopropanol mixed solution is added to prepare a product dispersion; in the polyethylene glycol / isopropanol mixed solution, the volume ratio of polyethylene glycol to isopropanol is 0.5-2.0:
1.
8. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (4), the concentration of the ion exchange product in the product dispersion is 0.005-0.01 g / mL.
9. The metal ion doping method for enhancing the electrochromic cycle stability of titanium dioxide according to claim 1, characterized in that: In the step (4), the calcination temperature is 350-500°C and the calcination time is 2-4 h.
10. A metal ion doped titanium dioxide film, characterized in that: The method is as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Fluorine-doped titanium dioxide nano array electrochromic film and preparation method thereof
CN109704592A
Porous crystalline / amorphous titanium dioxide electrochromic material as well as preparation method and application thereof
CN113736445A
Tungsten trioxide-titanium dioxide electrochromic film and preparation method thereof
CN113800781A